Changes

Jump to navigation Jump to search
95 bytes added ,  01:31, 29 September 2015
Line 540: Line 540:     
{|
 
{|
|<math display="inline">\alpha_2=ml^2+I\approx ml^2</math>
+
|<math display="inline">\alpha_2=ml^2+I</math>
 
|-
 
|-
 
|<math display="inline">\alpha_1=b</math>
 
|<math display="inline">\alpha_1=b</math>
Line 546: Line 546:  
|<math display="inline">\alpha_0=-mgl</math>
 
|<math display="inline">\alpha_0=-mgl</math>
 
|-
 
|-
|<math display="inline">\beta_4=(M+m)(ml^2+I)-m^2l^2\approx Mml^2</math>
+
|<math display="inline">\beta_4=(M+m)(ml^2+I)-m^2l^2</math>
 
|-
 
|-
|<math display="inline">\beta_3=(M+m)b+(ml^2+I)c\approx (M+m)b+ml^2c</math>
+
|<math display="inline">\beta_3=(M+m)b+(ml^2+I)c</math>
 
|-
 
|-
 
|<math display="inline">\beta_2=-(M+m)mgl+bc</math>
 
|<math display="inline">\beta_2=-(M+m)mgl+bc</math>
Line 567: Line 567:  
  g = 9.80665;
 
  g = 9.80665;
 
  b = 20;
 
  b = 20;
  G1 = tf([1], [T1 1])     # create transfer function model
+
  G1 = tf([m*l^2+I b m*g*l],
  G2 =  
+
        [(M+m)*(m*l^2+I)-m^2*l^2 (M+m)*b+(m*l^2+I)*c (M+m)*m*g*l+b*c m*g*l*c 0])
 +
  G2 = tf([m*l],
 +
        [(M+m)*(m*l^2+I)-m^2*l^2 (M+m)*b+(m*l^2+I)*c (M+m)*m*g*l+b*c m*g*l*c])
 
</syntaxhighlight>}}
 
</syntaxhighlight>}}
  
501

edits

Navigation menu